Oxidation of Dipeptide Glycylglycine by N-Bromosuccinimide in Aqueous Acetic Acid Medium and Comparison with Monomer Glycine: A Kinetic and Mechanistic Study - Pramila, K.; Anjaiah, Birla; Srinivas, P. (Asian Journal of Chemistry, 2012)
The oxidation reactions of dipeptide glycylglycine (GG) have been carried out with N-bromosuccinimide in presence of mercuric acetate. The kinetics revealed first order dependence on N-bromosuccinimide and fractional order dependence on glycylglycine. Michaelis-Menten type mechanism was proposed. Thermodynamic parameters have been evaluated. The oxidation reactions were compared to that of the monomer glycine.